Submarine record of volcanic island construction and collapse in the Lesser Antilles arc: First scientific drilling of submarine volcanic island landslides by IODP Expedition 340. (11th February 2015) - Le Friant, A.; Ishizuka, O.; Boudon, G.; Palmer, M. R.; Talling, P. J.; Villemant, B.; Adachi, T.; Aljahdali, M.; Breitkreuz, C.; Brunet, M.; Caron, B.; Coussens, M.; et al.
Abstract IODP Expedition 340 successfully drilled a series of sites offshore Montserrat, Martinique and Dominica in the Lesser Antilles from March to April 2012. These are among the few drill sites gathered around volcanic islands, and the first scientific drilling of large and likely tsunamigenic volcanic island‐arc landslide deposits. These cores provide evidence and tests of previous hypotheses for the composition and origin of those deposits. Sites U1394, U1399, and U1400 that penetrated landslide deposits recovered exclusively seafloor sediment, comprising mainly turbidites and hemipelagic deposits, and lacked debris avalanche deposits. This supports the concepts that i/ volcanic debris avalanches tend to stop at the slope break, and ii/ widespread and voluminous failures of preexisting low‐gradient seafloor sediment can be triggered by initial emplacement of material from the volcano. Offshore Martinique (U1399 and 1400), the landslide deposits comprised blocks of parallel strata that were tilted or microfaulted, sometimes separated by intervals of homogenized sediment (intense shearing), while Site U1394 offshore Montserrat penetrated a flat‐lying block of intact strata. The most likely mechanism for generating these large‐scale seafloor sediment failures appears to be propagation of a decollement from proximal areas loaded and incised by a volcanic debris avalanche. These results have implications for the magnitude of tsunami generation. Under some conditions, volcanic island landslide deposits composed of mainly seafloor sediment will tend to form smaller magnitude tsunamis than equivalent volumes of subaerial block‐rich mass flows rapidly entering water. Expedition 340 also successfully drilled sites to access the undisturbed record of eruption fallout layers intercalated with marine sediment which provide an outstanding high‐resolution data set to analyze eruption and landslides cycles, improve understanding of magmatic evolution as well as offshore sedimentation processes.